2014
DOI: 10.1108/tg-03-2014-0010
|View full text |Cite
|
Sign up to set email alerts
|

A vision of social media in the Spanish smartest cities

Abstract: Purpose – The purpose of this study is to analyse whether it is the Spanish urban environments that can be considered smart cities that are making the greatest efforts to ensure that citizens have better access to city information and, thus, participate to a greater degree in its governance. Design/methodology/approach – This analysis of the use made of social networks, as an integral part of democratisation, is divided into two phases: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 48 publications
0
10
0
4
Order By: Relevance
“…Both factors can be found in "Informational World Cities" (Stock, 2011) or "Smart Cities" (Shapiro, 2006), representing prototypical cities of the knowledge society (such as Singapore, New York or Hong Kong). Moreover, on a country level, Sáez-Martin et al (2014) found a direct relation between the "smartness" of a city and the social media adoption of its government. In Spain, "the 'smartest' smart cities are those which obtain the best overall results in terms of social networks" (Sáez-Martin et al, 2014, p. 521).…”
mentioning
confidence: 99%
“…Both factors can be found in "Informational World Cities" (Stock, 2011) or "Smart Cities" (Shapiro, 2006), representing prototypical cities of the knowledge society (such as Singapore, New York or Hong Kong). Moreover, on a country level, Sáez-Martin et al (2014) found a direct relation between the "smartness" of a city and the social media adoption of its government. In Spain, "the 'smartest' smart cities are those which obtain the best overall results in terms of social networks" (Sáez-Martin et al, 2014, p. 521).…”
mentioning
confidence: 99%
“…Based on these theories and previous literature, several factors have been traditionally considered: organizational size [28,71]; reputation [72]; location [73,74]; transparency and online activity [29], or communication and public participation [75]. This paper examines the most suitable factors related to the private and public sector as well as other aspects that are specific to the university sector: "Funding", "Size", "Transparency", and "Reputation".…”
Section: Explanatory Factors Of Stakeholder Engagementmentioning
confidence: 99%
“…Nenuostabu, kad šiame kontekste vis stipresnes pozicijas užima sumanumo koncepcijos vystymo ir praktinio panaudojimo reikšmė. Pastaroji koncepcija itin aktyviai plėtojama kalbant apie sumanius miestus, bendruomenę, ekonomiką, politiką, vyriausybę ir valdymą bei kitas sritis, neužmirštant ir sumanių regionų (Sáez-Martín, 2014;Iacobucci, 2014;Wolnicki, 2009;OECD report, 2013). Nors sumanumas sietinas su mokslo pažanga ir žiniomis grindžiamu valdymu, inovatyvumu, lankstumu, įtraukumu bei kitomis su konkurencingumu sietinomis charakteristikomis, remiantis A. S. Akopov ir G. L. Beklaryan (2014) galima pastebėti, kad būtent didelis skaičius sudėtingų tiesioginių ir grįžtamųjų ryšių tarp skirtingų regiono charakteristikų ir lemia sumanaus regiono koncepcijos apibrėžimo sudėtingumą ir valdymo komplikuotumą.…”
Section: įVadasunclassified